2014
DOI: 10.1371/journal.pone.0116423
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Thrombospondin-1 Modulates the Angioinflammatory Phenotype of Choroidal Endothelial Cells

Abstract: The choroidal circulation plays a central role in maintaining the health of outer retina and photoreceptor function. Alterations in this circulation contribute to pathogenesis of many eye diseases including exudative age-related macular degeneration. Unfortunately, very little is known about the choroidal circulation and its molecular and cellular regulation. This has been further hampered by the lack of methods for routine culturing of choroidal endothelial cells (ChEC), especially from wild type and transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…We have shown that reduced levels of TSP1 expression in EC in culture are generally associated with increased level of TSP2. 22,23 It is not known whether lack of TSP2 results increased level of TSP1. Here, we observed decreased levels of TSP1 expression in TSP2 null retina at various postnatal days when compared with TSP2 + / + mouse retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that reduced levels of TSP1 expression in EC in culture are generally associated with increased level of TSP2. 22,23 It is not known whether lack of TSP2 results increased level of TSP1. Here, we observed decreased levels of TSP1 expression in TSP2 null retina at various postnatal days when compared with TSP2 + / + mouse retina.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 However, whether lack of TSP2 results in increased expression of TSP1 remains unknown. Here, we examined the expression of TSP1 in retinas prepared from TSP2…”
Section: Lack Of Tsp2 Did Not Affect Retinal Tsp1 Expressionmentioning
confidence: 99%
“…This result was subsequently confirmed in choroidal endothelial cells (53). Choroidal capillary endothelial cells from the eyes of Thbs1 -/-mice had elevated phosphorylation of eNOS relative to WT cells, and intracellular NO in the null cells assessed using 4-amino-5-methylamino-2,7-difluorofluorescein (DAF) was sixfold higher than in WT cells.…”
Section: Fig 2 Overview Of Matricellular Protein Functions In Cellumentioning
confidence: 72%
“…However, a recent study reported elevated TSP2 levels produced by Thbs1 -/-choroidal endothelial cells despite having elevated eNOS phosphorylation and NO production as assessed by 4-amino-5-methylamino-2¢,7¢-difluorofluorescein diacetate fluorescence (53).…”
Section: No Signaling and Other Matricellular Proteinsmentioning
confidence: 92%
See 1 more Smart Citation